2018
DOI: 10.12737/article_5b5efa43c89ed2.10654942
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Oxides under the Urban Forest Crown Cover: Migration, Transformation, Real and Possible Environmental Consequences

Abstract: Has been presented the authors’ development demonstrating the possibility for determining the atmospheric air pollution in urban forest’s various areas by «passive» dosimetry’s methods. On the example of nitrogen oxides have been analyzed causes and consequences for technogenic pollution of forest ecosystems in urbanized areas. The study conducted on the territory of the Kuntsevskaya dacha’s spruce forest which is the part of the natural reserve «The Setun River’s Valley» (Moscow) has shown that in certain are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, the protection of nature at the present stage should be considered not so much as the preservation of individual organisms and communities, but mainly as the preservation of the natural processes of maintaining and regulating the cycle of substances and energy in the biosphere, which ensure the continuation of life on earth. Since vegetation (producers) is at the origin of all biogeochemical, ecological and energy processes in the biosphere, it is one of the most important components determining the well-being of the biosphere and life on earth [1,2,4,5,7,10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the protection of nature at the present stage should be considered not so much as the preservation of individual organisms and communities, but mainly as the preservation of the natural processes of maintaining and regulating the cycle of substances and energy in the biosphere, which ensure the continuation of life on earth. Since vegetation (producers) is at the origin of all biogeochemical, ecological and energy processes in the biosphere, it is one of the most important components determining the well-being of the biosphere and life on earth [1,2,4,5,7,10].…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that at the exposure of 0.014 mln -1 peroxyacetyl nitrates for four hours the leaves are damaged, 1 mln -1 peroxyacetyl nitrates for half an hour destroys chloroplasts. It is believed that the toxicity of peroxyacetyl nitrates is related to its ability to react with thiol groups (-SH), which are part of enzymes ensuring the action of chloroplasts [1][2][3][4][5]10].…”
Section: Exposure To Other Pollutants (Dust Ethylene Perchlorates Per...mentioning
confidence: 99%
See 1 more Smart Citation